PENGELOLAAN DANA DESA DALAM PEMBANGUNAN NAGARI PIOBANG KECAMATAN PAYAKUMBUH KABUPATEN LIMA PULUH KOTA - Hendry Junaidy; Berian Hariadi (Jurnal Administrasi Publik dan Pemerintahan, 2023)
The purpose of the research that the researchers conducted was to describe the Management of Village Funds in the Development of Nagari Piobang, Kecamatan Payakumbuh, Kabupaten Lima Puluh Kota (a case study of the community and the Nagari Piobang Government), describe the obstacles and efforts of the Nagari Government to have good planning in allocating Village Funds. Through development, of course, development can be felt by the entire village community. Or labor-intensive programs, which make people productive. The research that the author conducted uses qualitative research, where qualitative data analysis is an analytical process consisting of three streams of activities that occur simultaneously, namely data reduction, data presentation and conclusion drawing or verification. From the results of the research that the researchers did, it can be concluded that the situation in the field has not been in accordance with the expectations of the government, this is evidenced that only a small part of the Village Fund activities is used for the field of community empowerment in Nagari Piobang, because of the socialization and information provided to the people of Nagari Piobang still very little which results in a lack of interest in community participation